The Effect of Different Foundation Materials on the Color of Monolithic Zirconia at Different Thicknesses - Elham Ansarifard; Mina Mohaghegh; Maryam Pakniyat Jahromi; Rashin Giti (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Monolithic zirconia restoration has been introduced to overcome the porcelain chipping. Different factors can affect the color of monolithic zirconia, so achieving the desired color in the restorations is considered as a challenge. Purpose: The purpose of this in vitro study was to determine the effect of different foundation materials on the color of monolithic zirconia at different thicknesses. Materials and Method: In this experimental study, thirty ceramic disks in three thicknesses (i.e. 0.6mm, 1.1mm and 1.5mm) were fabricated from high translucency shade A2 monolithic zirconia block. Disk shaped foundation materials were fabricated from nickel chromium alloy (Ni-Cr), non-precious gold alloy (NPG), zirconia, and shade A2 composite resin. The color was measured by a spectrophotometer. The color differences (∆E) in the control and the test groups were calculated. The data were analyzed using two way ANOVA and compared with the posthoc Tukey test (a=0.05). Results: ceramic thickness and foundation materials had a significant effect on the mean values of ∆E of monolithic zirconia ceramics (p= 0.001). The highest amount of ∆E value was observed in NPG, while Ni-Cr resulted in the lowest ∆E. Unacceptable results (∆E>2.25) were observed for monolithic zirconia ceramics on NPG foundation material with a thicknesses of 0.6 and 1.1mm. The mean L* values of all foundation materials were higher than those of the control group except for Ni-Cr. The highest a* was seen in NPG and the mean b* values of all tested foundation materials were higher than those of the control group except for Ni-Cr. Conclusion: Increasing the thickness of monolithic zirconia decreased the color mismatch. High translucent monolithic zirconia could mask the color of Ni-Cr and zirconia in all three thicknesses (∆E˂2.25), while it could not mask the color of NPG under thickness of 1.5mm.